To bi or not to bi: Acute erythroid leukemias and hematopoietic lineage choice - di Genua, C; Nerlov, C (Elsevier, 2021)
Acute erythroid leukemia (AEL) is an acute leukemia characterized by erythroid lineage transformation. The WHO 2008 classification recognized two subtypes of AEL: bi-lineage erythroleukemia (erythroid/myeloid leukemia) and pure erythroid leukemia. In the updated 2016 WHO classification the erythroleukemia subtype was removed with around half of cases re-classified as myelodysplastic syndrome (MDS) and half as acute myeloid leukemia (AML). Diagnosis and classification are currently based on morphology using standard blast cutoffs, without integration of underlying genomic and other molecular features. Key outstanding questions are therefore whether AEL can be accurately diagnosed solely based on morphology or whether genetic or other molecular criteria should be included in its classification, and whether considering AEL as an entity distinct from AML and MDS is clinically relevant. We will here discuss recent work on the molecular basis of AEL, including the identification of mutations causative of AEL, and of transcriptional and epigenetic features that can be used to distinguish AEL from MDS and non-erythroid AML, and the prognostic value of these molecular features.